Prospective validation of the SCAI shock classification: Single center analysis. Issue 7 (7th October 2020) - Baran, David A.; Long, Ashleigh; Badiye, Amit P.; Stelling, Kelly
Abstract: Background: The Society for Cardiac Angiography and Interventions (SCAI) Shock Classification has been retrospectively validated by several groups. We sought to prospectively study outcomes of consecutive patients with reference to initial SCAI Shock Stage and therapeutic strategy as well as 24 hr SCAI Shock Stage reassessment. Methods: Kaplan Meier method was used to describe survival and Cox Proportional hazards modeling used to assess predictors of survival. Results: Over an 18‐month period, 166 patients were referred for evaluation. Demographics, hemodynamics, and most laboratory findings were similar between SCAI stages, which were assigned by the team. Initial SCAI Stage was a strong predictor of survival. Thirty‐day survival was 100, 65.4, 44.2, and 60% for patients with initial SCAI shock stage B, C, D, and E respectively ( p = .0004). Age and initial SCAI Shock Stage were shown to be the strongest predictors of survival by Cox proportional hazards. Mode of mechanical circulatory support (MCS) or lack of such was not a predictor of outcome. Shock stage at 24 hr was also examined. Thirty‐day survival was 100, 96.7, 66.9, 21.6, and 6.2% for patients with 3–4 SCAI stage improvement, 2 stage improvement, 1 stage improvement, no change in SCAI stage and worsening of SCAI stage respectively ( p  < .0001). Conclusions: Initial SCAI Shock stage predicts the survival of unselected patients with a variety of MCS interventions and medical therapy alone. The 24‐hr reassessment of shock stage further refines the prognosis.